Mediatization of Contemporaneity and the Processes of Socialization and Upbringing - Justyna Dobrołowicz (Nicolaus Copernicus University in Toruń, 2015)
The aim of this article is the analysis of processes of socialization and upbringing which take place in the contemporary, pre-figurative culture (dominated by the mass media). The main question of this article is: what are the threats to the process of socialization caused by mediatization of social contemporaneity?